The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1021/acs.jcim.2c01485
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Bioactive Therapeutic Peptide Generation and Screening

Abstract: Many bioactive peptides demonstrated therapeutic effects over complicated diseases, such as antiviral, antibacterial, anticancer, etc. It is possible to generate a large number of potentially bioactive peptides using deep learning in a manner analogous to the generation of de novo chemical compounds using the acquired bioactive peptides as a training set. Such generative techniques would be significant for drug development since peptides are much easier and cheaper to synthesize than compounds. Despite the lim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Plisson et al, applied several machine learning algorithms to hemolytic peptide and antimicrobial peptide datasets and emphasized that gradient boosting and extreme gradient boosting classifiers performed the best and even proposed 34 high-confidence nonhemolytic natural AMPs (Plisson et al 2020 ). A more recent approach has shown that by enhancing the effectiveness of machine learning methods with molecular docking and dynamics simulations, it is possible to develop fine-tuned peptide designs that can achieve the desired biological activity (Zhang et al 2023 ). In particular, the use of machine/deep learning methods, which are frequently used in the design of anticancer and microbial peptides and in the study of protein‒peptide interactions, in the design of novel therapeutic molecules for CAD could lead to significant advances (Varadi et al 2022 ; Jumper et al 2021 ; Lei et al 2021 ).…”
Section: In Silico Methods For Peptide Designmentioning
confidence: 99%
“…Plisson et al, applied several machine learning algorithms to hemolytic peptide and antimicrobial peptide datasets and emphasized that gradient boosting and extreme gradient boosting classifiers performed the best and even proposed 34 high-confidence nonhemolytic natural AMPs (Plisson et al 2020 ). A more recent approach has shown that by enhancing the effectiveness of machine learning methods with molecular docking and dynamics simulations, it is possible to develop fine-tuned peptide designs that can achieve the desired biological activity (Zhang et al 2023 ). In particular, the use of machine/deep learning methods, which are frequently used in the design of anticancer and microbial peptides and in the study of protein‒peptide interactions, in the design of novel therapeutic molecules for CAD could lead to significant advances (Varadi et al 2022 ; Jumper et al 2021 ; Lei et al 2021 ).…”
Section: In Silico Methods For Peptide Designmentioning
confidence: 99%
“…Numerous data-driven computational methods, particularly artificial intelligence (AI)-based support vector machine (SVM), random forest (RF), extremely randomized trees (ERTs), and deep learning (DL), have been developed to assist in predicting a large pool of therapeutic peptides based on peptide datasets generated by high-performance sequencing [138,139]. For instance, deep learning models for peptide generation such as DeepImmuno-GAN (architecture developed for generating potential MHC-binding peptides) [140], DeepACP and XDeep-AcPEP (for identifying and predicting activities of anticancer peptides) [141,142], ProteinGAN [143], HydrAMP [144], peptide VAE [145], pepGAN [146], and pepVAE [147] have been developed [148].…”
Section: Ai-driven Approaches For Peptide Discoverymentioning
confidence: 99%
“…Datasets. Following previous studies (Thi Phan et al 2022;Zhang et al 2023a), we collected therapeutic peptide data from public databases, containing two biological types, i.e., antimicrobial peptides (AMP) and anticancer peptides (ACP). Among these collected peptides, a portion of them only have 1D sequence information, without 3D structure information.…”
Section: Experiments Experimental Setupsmentioning
confidence: 99%